Supramolecular interaction facilitated small molecule films for organic field effect transistors - Arulkashmir, Arulraj; Mahale, Rajashree Y.; Dharmapurikar, Satej S.; Jangid, Manoj K.; Krishnamoorthy, Kothandam (Polymer Chemistry, 2012)
Metalloporphyrins and metal free porphyrins have been explored as active materials in field effect transistors. Amorphous forms of these porphyrins are preferred over their crystalline analogue due to the ease of solution processability. To achieve solution processability, a metalloporphyrin was anchored on a vinyl polymer by taking advantage of the supramolecular interaction between the metal and the pyridine moiety of the polymer. Non covalent bonding was preferred because it provides an opportunity to better manipulate the polymer's properties compared to its covalent bonding analogue. The binding between the porphyrin and the polymer was optimised in solution and the supramolecular complex was spun on various substrates to form thin films. The porphyrin was found to be uniformly distributed throughout the polymer films contrary to the existing approaches, wherein small molecule phase segregates in the polymer film. Field effect transistors were fabricated using the porphyrin-polymer complex and the device parameters were measured at atmospheric condition. The devices annealed at 80 degrees C showed hole carrier mobility of 2.0 x 10(-4) cm(2) V-1 s(-1) with charge trapping at the dielectric semiconductor interface. Furthermore, the high carrier mobility observed at low temperature annealing makes this supramolecular complex an attractive candidate to explore in flexible substrates.

Seeded on-surface supramolecular growth for large area conductive donor-acceptor assembly - Goudappagouda; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam; Gosavi, Suresh W.; Babu, Sukumaran Santhosh (Chemical Communications, 2015)
Charge transport features of organic semiconductor assemblies are of paramount importance. However, large-area extended supramolecular structures of donor-acceptor combinations with controlled self-assembly pathways are hardly accessible. In this context, as a representative example, seeded on-surface supramolecular growth of tetrathiafulvalene and tetracyano-p-quinodimethane (TTF-TCNQ) using active termini of solution-formed sheaves has been introduced to form an extended assembly. We demonstrate for the first time, the creation of a large-area donor-acceptor assembly on the surface, which is practically very tedious, using a seeded, evaporation-assisted growth process. The excellent molecular ordering in this assembly is substantiated by its good electrical conductivity (similar to 10(-2) S cm(-1)). The on-surface assembly via both internally formed and externally added sheaf-like seeds open new pathways in supramolecular chemistry and device applications.

Synthesis, optoelectronic, and transistor properties of BODIPY- and cyclopenta[c]thiophene-containing pi-conjugated copolymers - Debnath, Sashi; Singh, Saumya; Bedi, Anjan; Krishnamoorthy, Kothandam; Zade, Sanjio S. (Journal of Physical Chemistry C, 2015)
Three new low-band-gap copolymers were synthesized by fusing dipyrromethene difluoroborane (BODIPY) as the acceptor (A) and thiophene-capped 5,5-bis(hexyloxymethyl)-5,6-dihydro-4H-cyclopenta[c]-thiophene (CPT) as the donor (D). The BODIPY unit was copolymerized through the `alpha' positions (1 and 7 positions) in P1 and through the `beta' positions (2 and 6 positions) in P2 and P3. The additional acetylene unit between D and A in P3 enhanced the conjugation by minimizing the possible steric hindrance compared to that in P2, whereas P1 exhibited a more red-shifted absorption than P2 and P3 because of the more effective conjugaion through the `alpha' positions of BODIPY. Importantly, the optical band gaps (E-g(opt)) obtained from the onset of the absorption spectra are 1.28, 1.71, and 1.57 eV for P1, P2, and P3, respectively. P1 has the lowest band gap for any CPT-containing polymer. In the best transistor devices, a mobility improvement by 4 orders of magnitude from 3.22 x 10(-6) cm(2) V-1 s(-1) for P2 to 0.01 cm(2) V-1 s(-1) for P1 was achieved. DFT calculations alongside measured charge-transport properties indicated that appreciable alterations in the optoelectronic properties of the polymers were achieved through minor changes in their structural features. The polymers were further characterized by thin-film X-ray diffraction, atomic force microscopy, and spectroelectrochemistry to investigate their material and electrochemical properties.

Selenium-containing fused bicyclic heterocycle diselenolodiselenole: field effect transistorstudy and structure property relationship - Debnath, Sashi; Chithiravel, Sundaresan; Sharma, Sagar; Bedi, Anjan; Krishnamoorthy, Kothandam; Zade, Sanjio S. (ACS Applied Materials & Interfaces, 2016)
The first application of the diselenolodiselenole (C4Se4) heterocycle as an active organic field effect transistor materials is demonstrated here. C4Se4 derivatives (2a-2d) were obtained by using a newly developed straightforward diselenocyclization protocol, which includes the reaction of diynes with selenium powder at elevated temperature. C4Se4 derivatives exhibit strong donor characteristics and planar structure (except 2d). The atomic force microscopic analysis and thin-film X-ray diffraction pattern of compounds 2a-2d indicated the formation of distinct crystalline films that contain large domains. A scanning electron microscopy study of compound 2b showed development of symmetrical grains with an average diameter of 150 nm. Interestingly, 2b exhibited superior hole mobility, approaching 0.027 cm(2) V-1 s(-1) with a transconductance of 9.2 mu S. This study correlate the effect of p-stacking, Se center dot center dot center dot Se intermolecular interaction, and planarity with the charge transport properties and performance in the field effect transistor devices. We have shown that the planarity in C4Se4 derivatives was achieved by varying the end groups attached to the C4Se4 core. In turn, optoelectronic properties can also be tuned for all these derivatives by end-group variation.

Site-selective synthesis and characterization of BODIPY-acetylene copolymers and their transistor properties - Debnath, Sashi; Singh, Saumya; Bedi, Anjan; Krishnamoorthy, Kothandam; Zade, Sanjio S. (Journal of Polymer Science Part A-Polymer Chemistry, 2016)
To study the effect of site-selective copolymerization of borondipyrromethene (BODIPY) with acetylene on the structural and optoelectronic properties, three copolymers P1-P3 were synthesized by the Sonogashira cross-coupling of BODIPY units with diacetylene and bromine capping through all the possible linkages: alpha-alpha (P1), alpha-beta (P2), and beta-beta (P3). The optoelectronic properties of the polymers were investigated systematically to understand the effect of site-selective polymerization. The HOMO levels of the polymers were significantly tuned from P1 to P3 with negligible change in the LUMO levels. Broadening of absorption spectra from P3 to P1 was observed because of increase in the extent of conjugation. Additionally, the charge transport properties of these polymers in organic thin-film transistors (OTFTs) revealed that P1 and P3 exhibited only p-type mobility, whereas P2 exhibited electron mobility. Notably, the further investigations of the surface morphology of polymer films by atomic force microscopy (AFM) unveiled that comb like nanostructural arrangements in P3 was beneficial for the charge-carrier mobility over the circular arrangements in P1 and P2. (C) 2016 Wiley Periodicals, Inc.
Keywords: acetylene; BODIPY; DFT; low-band gap

Synthesis and characterization of simple cost-effective trans-A(2)BC porphyrins with various donor groups for dye-sensitized solar cells - Kumar, Ravi; Sankar, Muniappan; Sudhakar, Vediappan; Krishnamoorthy, Kothandam (New Journal of Chemistry, 2016)
We have designed and synthesized a series of simple cost-effective 'push-pull' Zn(II) porphyrin dyes containing various electron donors such as 2-thienyl, pyrenyl, phenyl, 4'-bromophenyl, 4'-tbutylphenyl and 4'-carboxyphenyl acceptor moieties in three steps. Their optical absorption spectra, electrochemical redox and photovoltaic properties have been investigated in detail. The overall power conversion efficiencies (Z) of DSSCs based on these dyes are in the range of 2.1 to 4.2% and highly depend on their donor moiety. The incorporation of trans-10,20-dimesityl groups is highly beneficial for preventing the p-p aggregation among the porphyrin moieties, thus favorably suppressing the charge recombination and intermolecular interaction. Among all, pyrenyl appended Zn(II) porphyrin has exhibited a higher power conversion efficiency of 4.2% under 1 sun illumination due to the extended p-conjugation and electron donating ability of the pyrenyl moiety.

Self-assembled spheres, flowers, and fibers from the same backbone and similar side chains - Singh, Anup Kumar; Krishnamoorthy, Kothandam (Langmuir, 2017)
Rylene imides (Ms) self-assemble into various nanostructures. Often, the synthesis of unsymmetrical RIs (URIs) is required to achieve nanostructures. However, the synthesis of URIs is nontrivial. Thus, a structurally similar alternative is desirable. iso-Indigo (i-indigo) has a pi core and lactam rings that are structurally similar to the RIs. Unsymmetrical iso-indigo (i-indigo) can be easily synthesized by condensing oxindole and isatin. We have synthesized a series of unsymmetrical i-indigo molecules. In these molecules, the pi-pi interaction, hydrogen bonding, and van der Waals interactions are in operation. Because of these, the molecules self-assemble into spheres, fibers, and dahlia flower morphologies. If the hydrogen bonding interaction is disrupted, then all of them form fibers. Control experiments indicate that the complete absence of hydrogen bonding is deleterious to self-assembly. We also show that the lower analogs of i-indigo are not sufficient to form self-assembled nanostructures.

Silk cocoon as counter - electrode substrate in dye - sensitized solar cells - Sudhakar, Vediappan; Das, Chayanika; Krishnamoorthy, Kothandam (ChemistrySelect, 2018)
Electrodes are vital components of energy conversion devices such as dye sensitized solar cells (DSSCs). The widely used electrodes consist of fluorine doped tin oxide (FTO) and platinum. We were interested in identifying a substrate that is available from natural resources and exhibit performance comparable to that of Pt coated FTO (Pt-FTO). Silk fibers are naturally available and they are mechanically stable. The woven silk fibers are known as silk cocoons (SCs) that structurally resemble widely used carbon paper electrodes. To impart conductivity to the insulating SCs, metal film was coated by an electroless metal plating procedure using polyphenols from green tea. The metal coated SCs were conformaly coated with a conjugated polymer and these electrodes were used as flexible electrodes in DSSCs. The flexible electrode based DSSCs exhibited a power conversion efficiency of 7.2% which is comparable to that of the DSSCs with rigid Pt-FTO based devices (7.4%).
Keywords: counter electrode; PEDOT-G-SCs; Recombination; Silk cocoons (SCs)

Steric and electronic effect in unsymmetrical squaraine dyes for dye-sensitized solar cells - Nawghare, Indrajeet S.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of physical chemistry C, 2023)
Functionalizing the light harvesting sensitizers with additional electron-donating or -withdrawing groups is a potential approach to modulate the photophysical and electrochemical properties which in-turn optimizes the driving force associated with the charge injection and dye-regeneration processes at the dye-TiO2/electrolyte interface and the photovoltaic device performance in dye-sensitized solar cells (DSSCs). Furthermore, modulated electronic levels of the dyes provide an opportunity to reduce the overpotential associated with the dye-regeneration process and make the dye-TiO2 interface compatible with various electrolytes. Furthermore, an in-built steric feature by means of introducing linear/branched alkyl groups in the sensitizer is important in controlling the aggregation of dyes on the TiO2 surface. Hence, to integrate both steric and electronic properties, a series of alkyl group-wrapped unsymmetrical squaraine dyes (SQ-X) with electron-donating and -withdrawing groups have been designed, synthesized, and utilized for DSSC device fabrication. These dyes are functionalized with alkyl groups at both sp(3)-C and N-atoms of the indoline donor moiety at the nonanchoring side to have a similar steric feature. Photophysical and electrochemical studies revealed that the HOMO and LUMO energy levels of the SQ-X series of dyes have been modulated systematically with sufficient driving forces for both charge injection and dye-regeneration processes with iodolyte (I-/I-3(-)) electrolyte. In the presence of electron-donating groups in SQ-X (where X = -NPh2 and -OMe), the HOMO energy levels are less positive than SQ-H, whereas the presence of electron-withdrawing groups such as -CO2Me, -CN, and -NO2 pushed the HOMO energy levels toward more positive potentials. Enhanced photovoltaic performances have been obtained for the dyes containing electron-donating groups, where the dye with the -NPh2 group showed a maximum of eta 7.03% (V-OC 708 mV, J(SC) 13.16 mA cm(-2), and ff 78%). The dye with the strong electron-withdrawing group -NO2 showed an efficiency of 1.49% (V-OC = 634 mV, J(SC) = 3.13 mA cm(-2), and ff 75%). As the dyes with the electron-withdrawing group possess deep positive HOMO energy levels, the DSSC device characterization has been investigated with the Cu+/2+ redox shuttle. The reduced device performance of electron-withdrawing-group-containing dyes is due to the unfavored charge distribution in the LUMO compared to the presence of electron-donating-group-containing dyes, and it was supported by the difference in the charge injection efficiency.
Keywords: cobalt; Donor; Dynamics; Organic dyes

Shuttle balance between lithiophilic functionalities substituted on conjugated polymers to improve lithium-ion diffusion and cycling stability of batteries - Kargude, Radhakisan; Javaregowda, Bharathkumar H.; Palani, Sathishkumar; Singh, Anup K.; Krishnamoorthy, Kothandam (Macromolecules, 2024)
Herein, we report the design and synthesis of i-Indigo and trans-1,2-di(2-thienyl)ethylene (TVT) comprising copolymers with various side chains that are used as anode-cum-binder in Li-ion batteries. The TVT disrupts the crystallinity, and the i-Indigo renders the handle for unsymmetrical substitution. Polymer P1 comprises alkyl chains on i-Indigo, whereas P2 comprises an alkyl chain and a chain with a urethane moiety as another side chain. Polymer P3 comprises i-Indigo with a urethane moiety and triethylene glycol as side chains. The i-Indigo in P4 is substituted with triethylene glycol and alkyl chains as side chains. These polymers were found to be amorphous with pi-pi stacking due to the extremely small torsional angle imparted by TVT moieties. All of these polymers showed comparable specific capacity while used as an anode in Li-ion batteries due to the presence of a common conjugated backbone. However, the battery metrics varied significantly while the current density of the batteries varied between 0.1 and 2.0 A g(-1). P1 and P2 showed a very close recovery of specific capacity at 0.1 A g(-1) before and after various current densities. However, polymers P3 and P4 did not recover from the specific capacity fading due to the presence of triethylene glycol side chain that degraded. Polymer P2 with an alkyl side chain and a chain with a urethane moiety showed stable performance over 2000 charge-discharge cycles. Contrary to this, the stability of polymers with triethylene glycol side chains decreased over 2000 charge-discharge cycles. Polymer P2 with a urethane side chain also showed improved Li-ion diffusion because the urethane moiety facilitated better Li-ion transport.

Synergistic effect of lactam and pyridine nitrogen on polysulfide chemisorption and electrocatalysis in lithium sulfur batteries - Javaregowda, Bharathkumar H.; Kargude, Radhakisan; Birajdar, Sarika; Shivankar, Bhavana; Krishnamurty, Sailaja; Jones, Lathe A.; Caruso, Rachel A.; Krishnamoorthy, Kothandam (ACS APPLIED MATERIALS & INTERFACES, 2024)
Keywords: Li-S battery; phenyl-diketopyrrolopyrrole; pyridine-diketopyrrolopyrrole